Muslim disunity and lost in the first crusade - Alatas, Alwi; Mansor Majdin, Mohamad Firdaus (UTM Press, 2022)
The Frankish army in the First Crusade were moved by the call of Pope Urban II in 1095. Over the next four years, they succeeded in capturing important cities in Asia Minor and al Shām (Greater Syria), such as Nicaea, Edessa, Antioch and Jerusalem. The strength of the crusading forces was actually not greater than that of the Muslims and they were also not advanced in term of culture and science vis-a-vis the Muslims. In hindsight, this shows that there were other reasons that caused the defeat of the Muslims during the First Crusade. This study uses historical analysis as its methodology to see the correlation between the defeat of the Muslims and the political division that was prevailing among them during the First Crusade. This study suggests that there is a strong correlation between disunity and the defeat of the Muslims during the First Crusade.